Analysis of Optic Nerve Types in Relation to Posterior Paranasal Sinuses: A Computed Tomographic (CT) Study - Mubina Lakhani; Muhammad Ali; Madeeha Sadiq (KARACHI MEDICAL AND DENTAL COLLEGE, 2017)
Objective: To assess the variations in  the  course  of  optic  nerve  (ON)  in  relation  to  sphenoid  sinus with the help of CT scan. Methodology: A cross-sectional study was carried out using  computed  tomographic  (CT)  paranasal  sinus scans of two hundred and seventy study participants between January 2017 and May 2017. Non-probability consecutive sampling technique was used and data was entered on SPSS version 23. Inclusion criteria comprised of adults coming for CT head and  brain  who  did  not  have  bony  abnor- mality of sphenoid and ethmoid sinuses or adjacent structures. However, individuals  with  sinonasal  tumors, chronic rhinosinusitis, prior sinus surgery, facial fracture, nasal polyposis and  congenital  craniofacial anomaly were excluded from this study. Analysis of optic nerve was carried out according to DeLano's classification. Results: Type 1 ON was found to be the most frequent type; 55.93%, followed by type 2 with a frequency of 26.85%. However, type 3 and type 4 appeared less frequently, that is 11.1% and 6.11%, re- spectively. When comparing right and left sides it was noted that the frequency of type 1 optic nerve was found to be higher on both right and left sides with a value of 56.30% and 55.5%, respectively. Type 2 showed a frequency of 26.67% on right side and 27% on left side. Type 3 was identified to be   11.4% and 10.7% on right and left sides, respectively. Type 4 optic nerve was found to be the least  common type in our study on both sides, i.e. 5.56% on the right side and 6.67% on the left side. Conclusion: The combined percentage of type II and type III ON that is 37.96% in our sample brings us to this conclusion that  fairly  high  percentage  of  our  population  is  exposed  to  increased  potential risk of iatrogenic optic nerve injury thus emphasising the need for careful evaluation of ON in relation to sphenoid sinus anatomy on CT scan prior to endoscopic sinus surgery.